REDUCING COMPANYâS LOGISTIC COST BY OPTIMIZING TRANSPORTATION COST IN BANDUNG CITY. A CASE STUDY OF 8 LIMA LOGISTIK - Prajna Adistana, Edwin
One of the most effective way to reduce logistic cost is by optimizing transportation cost as it impacts about 50% of the logistic cost. As a start-up company that provides distribution logistic services in Bandung Area to 7 tenants, 8 Lima Logistik has many constraints due to the limited resources, such as: amount of the vehicle, vehicle’s capacity, delivery time per week, Bandung’s traffic condition, and the random date of order from the existing customers. This research aims to find delivery route with the lowest cost for 8 Lima Logistik with the company’s constraints in order to optimize its transportation cost. The authors gathered the primary data by conducting interview to the 8 Lima Logistic and observing the company’s existing delivery route’s policy. Secondary data was collected from google maps to find the approximate distance from warehouse to tenants, tenants to the other tenants, and tenants to warehouse. The gathered data was analyzed using Genetic Algorithm and Nearest Neighbor Procedure method. The Result shows that Genetic Algorithm method gives lower transportation cost compared with Nearest Neighbor Procedure’s. This result could also be used by the other company that has similar problem and condition with 8 Lima Logistik.